Answer:
3 sin(41t) - 3 sin(t)
Explanation:
The general formula to convert the product of the form cos(a)sin(b) into sum is:
cos(a) sin(b) = 0.5 [ sin(a+b) - sin (a-b) ]
The given product is:
6 cos(21t) sin(20t) = 6 [ cos(21t) sin(20t) ]
Comparing the given product with general product mentioned above, we get:
a = 21t and b = 20t
Using these values in the formula we get:
6 cos(21t) sin(20t) = 6 x 0.5 [ sin(21t+20t) - sin(21t-20t)]
= 3 [sin(41t) - sin(t)]
= 3 sin(41t) - 3 sin(t)
Therefore, second option gives the correct answer